2022
DOI: 10.3389/fcvm.2022.1001753
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical effects of subclinical leaflet thrombosis after transcatheter aortic valve replacement

Abstract: AimsThe number of trans-catheter aortic valve replacement (TAVR) procedure is increasing; However, the incidence of leaflet thrombosis is higher in TAVR than in surgical aortic valve replacement (SAVR). In this study, the risk factors for leaflet thrombosis after TAVR and its effects on hemodynamics and clinical course were investigated.Methods and resultsMultidetector computed tomography (MDCT) was performed at 1year after TAVR in 94 patients from January 2015 to October 2020 at Samsung Medical Center in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Thrombosis, which is often hypothesized to be a result of flow stagnation and unfavorable materials, leads to subclinical leaflet thickening, where the deposition of thrombosis on the aortic leaflet surface causes malfunctioning of the prosthesis. Rates of leaflet thrombosis are greatly varied with each device trial, with rates common rates between 10-15% and some studies reporting rates up to 40% of patients [5,6]. This discrepancy may be due to the lack of symptomatic or the impact on patient outcomes [7], leading to reduced detection rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombosis, which is often hypothesized to be a result of flow stagnation and unfavorable materials, leads to subclinical leaflet thickening, where the deposition of thrombosis on the aortic leaflet surface causes malfunctioning of the prosthesis. Rates of leaflet thrombosis are greatly varied with each device trial, with rates common rates between 10-15% and some studies reporting rates up to 40% of patients [5,6]. This discrepancy may be due to the lack of symptomatic or the impact on patient outcomes [7], leading to reduced detection rates.…”
Section: Introductionmentioning
confidence: 99%
“…With the extension of TAVR to younger patients, rates of subclinical leaflet thickening have been increasing [8][9][10]. Many studies [5,6] have shown rates of leaflet thrombosis are linked to unfavorable TAVR deployment parameters such as eccentric deployments [11] or reduced valve performance due to heavy patient calcification [12], as well as anatomical features such as large sinus of Valsalva leading to increased stagnation [13].…”
Section: Introductionmentioning
confidence: 99%